On Harmonically (p, h, m)-Preinvex Functions. (31st January 2017) - Wu, Shan-He; Baloch, Imran Abbas; İşcan, İmdat
Abstract : We define a new generalized class of harmonically preinvex functions named harmonically ( p, h, m ) -preinvex functions, which includes harmonic ( p, h ) -preinvex functions, harmonic p -preinvex functions, harmonic h -preinvex functions, and m -convex functions as special cases. We also investigate the properties and characterizations of harmonically ( p, h, m ) -preinvex functions. Finally, we establish some integral inequalities to show the applications of harmonically ( p, h, m ) -preinvex functions.